Lipomas of the central nervous system in the newborns – a report of eight cases - Gradowska, Kinga (International Scientific Literature, Inc., 2011)
BACKGROUND: Central nervous system lipomas are rare tumours. In most of the cases they are located in corpus callosum of the brain. The ultrasonographic image of lipomas tends to be quite characteristic. Final diagnosis is however done on a basis of brain resonance. The purpose of this work is to present proceeding in case of central nervous system lipomas with particular attention to diagnostic imaging. This work is based on own research. CASE REPORT: There are eight patients with central nervous system lipomas described in this work. The ultrasonographic imaging performed upon patients’ birth revealed features of agenesis of corpus callosum with presence of hyperechoic structure in the area of median line within corpus callosum. This image correlated with Nuclear Magnetic Resonance examination results. Our research confirms that patients with central nervous system lipomas represent rare diagnostic and therapeutic cases. Due to characteristic results of ultrasonographic imaging of the brain, recognition of agenesis of corpus callosum would not cause difficulties. However the presence of hyperechoic structure without vascular flow which may suggest lipomas of corpus callosum would require final verification of the diagnosis and wider assessment of brain with NMR examination. We did not recognize any relation between corpus callosum pathology and neuroinfection of cytomegalovirus etiology. In all of the eight research cases there were malformations diagnostics conducted. There were genetic irregularities in case of two of the neonates only. Until today, all of the patients remain under neurological care. Their psychomotor development is regularly controlled. CONCLUSIONS: Taking into consideration that numerous malformations occur altogether with brain lipomas, it is recommended to conduct appropriate diagnostics, to inform parents on an essence of diagnosis and on necessity of observing child’s psychomotor development. Obviously, it is crucial to secure a patient with paediatric and neurological care.